PEMANFAATAN KONTEN INSTAGRAM DALAM KAMPANYE POLITIK: ANALISIS KONTEN VISUAL @yashinta.istimewa - Dian Eka Permanasari (Jurnal Komunikasi dan Kajian Media, 2025)
This study examines the strategic use of Instagram as a visual communication tool in a political campaign context. The campaign analyzed focuses on building a candidate's image through three main content formats: images, videos, and mixed media (a combination of images and videos). The objective is to assess how these content formats and visual elements, such as color, typography, layout, and logo consistency, impact audience perception and engagement. Using a descriptive qualitative method, data is derived from detailed content analysis of campaign posts on Instagram. Findings reveal that images dominate the campaign's content due to their high visual impact and immediate recognition, while videos serve as complementary content to enhance emotional engagement. Key themes such as female empowerment, local culture, and sustainable transport innovations resonate well with the audience, strengthening the candidate’s image as a responsive and relatable figure. The study concludes that a combination of visually consistent elements and socially relevant themes in social media can effectively build a political candidate’s brand, fostering closer connections with the electorate. This approach offers insights into effective digital campaign strategies for future political communication.